WORK TEAM COHESIVENESS: REFINING THE CONCEPTUAL DEFINITION - Naibaho, Hastuti (IJBLE Scientific Publications Community Inc., 2023)
The results of studies on the relationship between work team cohesiveness and team performance are still not conclusive. Inconsistencies in the results, caused by a shifting conceptual definition, have become a problem in cohesiveness measurements. This inconsistency in a conceptual definition exists in the literature and is based on the antecedents or the consequences of team cohesiveness. This study aimed to test the conceptual definition of work-team cohesiveness that had been proposed and to build a measurement for work-team cohesiveness. The respondents of this study were work teams from manufacturing and services companies. The results of this study support the conceptual definition proposed by the author.